Importance of timing and repetition of stubble cultivation for post‐harvest control of Elymus repens. (26th November 2015) - Ringselle, B; Bergkvist, G; Aronsson, H; Andersson, L
Summary: Without herbicides, the control of Elymus repens relies on intensive tillage, often in the form of repeated post‐harvest stubble cultivations followed by ploughing. This is costly and time‐consuming and also increases the risk of nitrogen leaching. Our aim was to quantify the controlling effect on E. repens of single and repeated cultivation and differing time of cultivation in relation to spring cereal harvest. A 2‐year experiment was conducted at two sites in the south and east of Sweden in 2011–2012 and 2012–2013. We compared no, single and repeated tine cultivation followed by mouldboard ploughing; the single cultivation was performed directly after harvest or 20 days after harvest; when repeated, the first cultivation was performed immediately or 5 days after harvest, followed by a second cultivation 20 days after harvest. Tine cultivation in combination with mouldboard ploughing resulted in 50–70% lower rhizome biomass, and increased average subsequent cereal yields by 0–130% compared with ploughing alone. Large E. repens populations appeared to be more efficiently reduced by tine cultivation than smaller populations. A single tine cultivation 20 days after harvest tended to result in a higher E. repens shoot density and more rhizome biomass in the subsequent year than tine cultivation directly after harvest. Additional cultivation 20 days after harvest did not improve control of E. repens or the subsequent cereal grain yield, compared with a single cultivation conducted directly after harvest. In conclusion, preventing the growth of E. repens during the early part of the post‐harvest autumn period was more important than starving rhizomes with repeated cultivations.